PERANAN KOMUNIKASI PEMERINTAH DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KANTOR KELURAHAN ADIARSA BARAT KECAMATAN KARAWANG BARAT - Muhammad Rizki Rahmatullah; Dewi Noor Azijah; Rachmat Noor Ramdani (Peneliti.net, 2026)
This study is entitled the role of government communication in improving the quality of public services inthe Adiarsa Barat urban village of ice, Adiarsa Barat sub-district. This research uses Qualitative methods, qualitative methods of data search processes to understand social problems based on comprehensiveresearch (holistic), formed by words, and obtained from natural situations. This research uses Laswell'scommunication theory: 1. communicator, 2. message, 3. media, 4. communicant, 5. feedback. Service is the quality of service provided by public agencies to the community. In carrying out its functions, the government apparatus of Adiarsa Barat urban Village is quite good in carrying out its duties incommunicating and carrying out its duties, namely: Communicative, Responsive, fast and provide comfort and security. Comunication of government in Adiarsa Barat urban Village is the process ofexchanging information between the village government and the people of Adiarsa Barat. Thiscommunication involves delivering information related to government activities, public policies, social programs, and public services to the community. The purpose of village government communication to ensure that the people of Adiarsa Barat receive clear and accurate information about matters relatedtothe lives of the people of Adiarsa Barat.